STRATEGIC ENTREPRENEURSHIP DALAM PENINGKATKAN VOLUME PENJUALAN EKSPOR KENDANG “DJEMBE” PADA UD. BUDI LUHUR, KOTA BLITAR - Indria Guntarayana (Universitas Islam Balitar, 2018)
Djembe is an icon of Blitar City, this is because the largest djembe handicraft industry center is in Blitar City. UD. Budi Luhur in Blitar City, East Java is one of the SMEs in the wood craft industry. UD. Budi Luhur is an UKM that moves to market its djembe products by exporting to foreign countries. The purpose of this study was to describe how the entrepreneurial strategy of UD. Budi Luhur in entering and marketing its products on the international market. This study also explains the application of entrepreneurial strategies to UD. Budi Luhur in increasing the export sales volume of kendang djembe handicrafts, as well as alternatives to maintain the entrepreneurial strategy that has been applied by UD. Budi Luhur in dealing with international markets. The research method used in this study was descriptive with a qualitative approach. The data sources in this study are primary data by conducting interviews with the owners of UD. Budi Luhur and the Regional Cooperative and SME Office, Blitar City and focus group discussion (FGD) together with the Tanggung Village Bubut Kayu Association which is a working partner of UD. Budi Luhur and secondary data in the form of documents related to the theme of this research. The results showed that exports were chosen by UD. Budi Luhur to enter the international market. UD. Budi Luhur applies growth, innovation, network, harvest / exit strategies by reading opportunities to develop markets, innovating products, creating good relationships with buyers and being able to form profitable networks and working with similar companies to meet market demand so as to maximize sales and increase the volume of export sales.